Polarization-Insensitive, High-Efficiency Metasurface with Wide Reception Angle for Energy Harvesting Applications - Abdulrahman Ahmed Ghaleb Amer; Nurmiza Othman; Mohammed M. Bait-Suwailamn; Syarfa Zahirah Sapuan; Ali Ahmed Ali Salem; Adeb Salh (Sensors)
This research presents an innovative polarization-insensitive metasurface (MS) harvester designed for energy harvesting applications at 5 GHz, capable of operating efficiently over wide reception angles. The proposed MS features a novel wheel-shaped resonator array whose symmetrical structure ensures insensitivity to the polarization of incident electromagnetic (EM) waves, enabling efficient energy absorption and minimizing reflections. Unlike conventional designs, the metasurface achieves near-unity harvesting efficiency, exceeds 94% under normal incidence, and maintains superior performance across various incident angles for TE and TM polarizations. To validate the design, a 5 × 5-unit cell array of the MS structure was fabricated and experimentally tested, demonstrating excellent agreement between simulation and measurement results. This work significantly advances metasurface-based energy harvesting by combining polarization insensitivity, wide-angle efficiency, and high absorption, making it a compelling solution for powering wireless sensor networks in next-generation applications.